Impact of Close and Positive Margins in Transoral Laser Microsurgery for Tis–T2 Glottic Cancer - Fiz, Ivana; Mazzola, Francesco; Fiz, Francesco; Marchi, Filippo; Filauro, Marta; Paderno, Alberto; Parrinello, Giampiero; Piazza, Cesare; Peretti, Giorgio (Frontiers in Oncology, 2017)
Introduction: Transoral laser microsurgery (TLM) represents one of the most effective treatment strategies for Tis-T2 glottic squamous cell carcinomas (SCC). The prognostic influence of close/positive margins is still debated, and the role of Narrow Band Imaging (NBI) in their intraoperative definition is still to be validated on large cohort of patients. This study analyzed the influence of margin status on recurrence-free (RFS) and disease-specific survivals (DSS). Methods: We retrospectively studied 507 cases of pTis-T1b (Group A) and 127 cases of pT2 (Group B) glottic SCC. We identified the following margin status: negative (n=232), close superficial (n=79), close deep (n=35), positive single superficial (n=146), positive multiple superficial (n=94), and positive deep (n=48), and analyzed their impact on RFS and DSS. Close margins were defined by tumor-margin distance <1 mm. Pre-TLM margins were defined by white light in 323 patients, while NBI was employed in 311 patients. Results: In Group A, DSS and RFS were reduced in positive multiple superficial and positive deep margins (DSS=96.1% and 97%, both p<0.05; RFS=72%, p<0.001 and 75.8%, p<0.01). In Group B, DSS was reduced in positive multiple superficial margins (82.4%, p<0.05). RFS was reduced in positive single superficial, positive multiple superficial, and positive deep margins (62.5%, 41.2%, and 53.3%, p<0.01). In the entire population, RFS was reduced in close deep margins (77.1%, p<0.05). Use of NBI led to improvement in RFS and DSS. Conclusions: The study indicates that close and positive single superficial margins do not affect DSS. In contrast, all types of margin positivity predict the occurrence of relapses, albeit with different likelihood, depending on stage/margin type. Close deep margins should be considered as a single risk factor. Use of NBI granted better intraoperative margins definition.